Prikrita vplačila kapitala - premoženjski vložki kot podlaga povečanja premoženja družbe - Jovanovič, Dušan (Podjetje in delo, 2021)
In this article, the authors introduce us to an interesting legal issue, as an inverse pic-ture of disguised profit / contribution payments (Verdeckte Gewinnausschüttung), which in fact means an increase (and not a decrease) in the company's assets. This is not necessarily carried out in formal ways of increasing the company's capital through contributions that are monetary (in cash) or in-kind. A contrario we can increase the assets of a company also by so-called covert capital payments, which, however, may have some problems in the balance sheet, and especially in tax and accounting terms due to the "covertness". These contributions can also be of a monetary or material nature, but they represent an actual increase in the company's assets, which is beneficial for creditors and, despite its secrecy, can also have positive consequences for the tax authorities. The authors point out a comparable legal view of the corporate institute in German law and practice, which could have the same meaning and legal consequences in Slovenia, and with its placement and use would significantly contribute to the business practice of economic entities and its stakeholders, while representing a useful guide for tax treatment.
Keywords: capital increase; company assets; covert capital increase; davčno pravo; poslovni delež; povečanje kapitala; premoženje družbe; prikrito povečanje kapitala; share; tax law; ZGD-1